2013
DOI: 10.1111/jvh.12137
|View full text |Cite
|
Sign up to set email alerts
|

An integrated analysis of SOCS1 down‐regulation in HBV infection‐related hepatocellular carcinoma

Abstract: Persistent inflammation together with genetic/epigenetic aberrations is strongly associated with chronic Hepatitis B virus (HBV) infection-related hepatocarcinogenesis. Here, we investigated the alterations of the suppressor of cytokine signalling (SOCS) family genes in HBV-related hepatocellular carcinoma (HCC). A total of 116 patients with HCC were enrolled in this study. The methylation statuses of SOCS1-7 and CISH genes were quantitatively measured and clinicopathological significance of SOCS1 methylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 36 publications
(49 reference statements)
0
22
0
Order By: Relevance
“…In addition, SOCS1 and SOCS3 have been implicated in HCC (Niwa et al, 2005;Yoshida et al, 2004;Yoshikawa et al, 2001). The gene loss and epigenetic silencing of SOCS1 and SOCS3 frequently occurred in HBVrelated HCC patients (Niwa et al, 2005;Zhang et al, 2014). Moreover, one recent study reported that HBx could downregulate the expression of SOCS1 through enhancing the methylation of SOCS1 gene promoter (Fu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SOCS1 and SOCS3 have been implicated in HCC (Niwa et al, 2005;Yoshida et al, 2004;Yoshikawa et al, 2001). The gene loss and epigenetic silencing of SOCS1 and SOCS3 frequently occurred in HBVrelated HCC patients (Niwa et al, 2005;Zhang et al, 2014). Moreover, one recent study reported that HBx could downregulate the expression of SOCS1 through enhancing the methylation of SOCS1 gene promoter (Fu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous genes, such as SOCS1 (17), GSTP1 (26), SFRP1 (27), FOXD3 (28), SYK (29), FAM43B (30), which are involved in tumor suppression, cell cycle regulation, apoptosis, and DNA repair have been shown to be suppressed by DNA hypermethylation in HCC. In our study TRIM58 mRNA expression was significantly reduced in HCC tissues comparing with adjacent non-tumor tissues, while the assessment of DNA methylation by MSRE-qPCR demonstrated that TRIM58 methylation was significantly increased in HCC tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In HCC, Niwa et al revealed that SOCS3 was hypermethylated in 33.3% (6/18) of HCC tissues [ 20 ]. However, in our previous report, we did not observe SOCS3 hypermethylation in HBV-related HCC tissues [ 21 ]. These conflicting results may be due to the complicated etiological mechanism of HCC and the different detected loci in the SOCS3 promoter region.…”
Section: Introductionmentioning
confidence: 59%
“…The methylation primers of SOCS3 were as follows: Primer 1, forward: AGCTCGAGGGACGCGCGCGCGAA, reverse: CTGAGCCCCCTCGGGTC-CCCAAG; Primer 2, forward: GGTGCCCCAGTCGCTCGGCGAAG, reverse: GGAAGGCG-CGAGCGCGTTGAGTGC. The cut-off value was set at 10%, as previously report [ 21 ].…”
Section: Methodsmentioning
confidence: 99%